2015
DOI: 10.1016/j.pharep.2014.09.008
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and anticancer activity of 7-hydroxycoumarinyl gallates

Abstract: The novel compounds represent an excellent starting point for the further optimization and the design of therapeutically effective anti-cancerous drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The anticancer and cytotoxic activities of synthetic and natural coumarins with different functional groups on their basic structure (Figure 2) have been reported by several investigators. These studies showed the anticancer activity of coumarins against breast cancer [89], colon cancer [94], lung cancer [24], ovarian cancer [95], hepatocellular carcinoma [96], bladder carcinoma [97], leukemia [98], and other types of cancer in vitro and in vivo, via different mechanisms, including free-radical scavenging, antioxidant activity [99], induction of cell cycle arrest [100], interaction with various signaling pathways with important role in cell differentiation and proliferation [101], telomerase and carbonic anhydrase inhibition [102,103], and antiangiogenic activity [104]. For example, Taniguchi and co-workers [105] isolated eight coumarins from the leaves of Rhizophora mucronata and reported the anticancer effects of methoxyinophyllum P, calocoumarin B, and calophyllolide against HeLa cells (cervical cancer), with IC 50 equal to 3.8, 29.9, and 36.4 μM, respectively, and HL-60 cells (promyelocytic leukemia cells) with IC 50 of 12.9, 2.6, and 2.2 μM, respectively.…”
Section: Coumarinsmentioning
confidence: 99%
“…The anticancer and cytotoxic activities of synthetic and natural coumarins with different functional groups on their basic structure (Figure 2) have been reported by several investigators. These studies showed the anticancer activity of coumarins against breast cancer [89], colon cancer [94], lung cancer [24], ovarian cancer [95], hepatocellular carcinoma [96], bladder carcinoma [97], leukemia [98], and other types of cancer in vitro and in vivo, via different mechanisms, including free-radical scavenging, antioxidant activity [99], induction of cell cycle arrest [100], interaction with various signaling pathways with important role in cell differentiation and proliferation [101], telomerase and carbonic anhydrase inhibition [102,103], and antiangiogenic activity [104]. For example, Taniguchi and co-workers [105] isolated eight coumarins from the leaves of Rhizophora mucronata and reported the anticancer effects of methoxyinophyllum P, calocoumarin B, and calophyllolide against HeLa cells (cervical cancer), with IC 50 equal to 3.8, 29.9, and 36.4 μM, respectively, and HL-60 cells (promyelocytic leukemia cells) with IC 50 of 12.9, 2.6, and 2.2 μM, respectively.…”
Section: Coumarinsmentioning
confidence: 99%
“…Cell 79 Receptor Modeling and Ligand Docking. Our computational strategy for the structure-based design of AR ligands involves a combination of homology modeling, ligand−receptor docking, and free energy calculations, as recently reviewed.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The cytopathic changes induced by selected compounds in the PC-3 cell line were analyzed using confocal microscopy. 79 For the sake of comparison, the prototypic A 2B AR antagonist PSB603 34 was also included in superior to that observed for PSB603 (Figure 9A). Interestingly, the antimetastatic effect was in all cases lightly superior on PC-3 cells compared to DU145 and LNCaP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Then, the medium was replaced with fresh complete medium containing AITC (20 µM), SFN (30 µM), IB (30 µM), PEITC (4 µM) and/or DOCE (2 nM). After 72 h, PC-3 cells were stained according to previously published procedures [30]. Firstly, the treatments were replaced by PBS solution containing fluorescent dye CFDA-SE (Carboxyfluorescein diacetate succinimidyl ester, cat.…”
Section: Cytophatic Changesmentioning
confidence: 99%